RANCANGAN APLIKASI SMS GATEWAY UNTUK MENINGKATKAN PELAYANAN KEPADA PASIEN DI RUMAH SAKIT IBNU SINA MAKASSAR - Sahabuddin (PROGRESS, 2016)
Rumah Sakit Ibnu Sina Makassar is a large hospital that gives the servicing to patients. To increase servicing, the patient can registry through SMS Gateway. Through a program SMS calls "SMS RS Ibnu Sina," patients can order whatever they want a registration of ‘ Rawat Jalan dan Rawat Inap’ at any time they want, between the hours of 8 a.m. and 4 p.m. The program can send the billing statement for patients that have debt. The benefits of SMS RS Ibnu Sina go beyond patient satisfaction, and can reduce queue’s patients. Patients can send SMS of suggestion, claim.